2023
DOI: 10.1021/acscatal.3c02350
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Mediated Energy Transfer Enables Cyclopropanes Bearing Contiguous All-Carbon Quaternary Centers

Abstract: Cyclopropanes bearing contiguous all-carbon quaternary centers continue to attract attention due to their bioactivities. However, methods to obtain cyclopropanes with contiguous all-carbon quaternary centers remain largely unexplored due to the high steric hindrance of these compounds. Herein, we report a visible-light-mediated energy-transfer (EnT) strategy to realize in situ donor/donor carbenes from readily available N-tosylhydrazones, facilitating the synthesis of highly congested EWG-free cyclopropanes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…In this context, we became inspired by some recent publications that reported that the decomposition of N -tosylhydrazones can be promoted photochemically. 17–20 In particular, König et al discovered that the formation of diazo compounds from N -tosylhydrazones can be achieved by irradiation of the N -tosylhydrazone salts with visible light at rt, and applied this reaction in the homologation of carbonyl compounds (Scheme 1e). 17 Taking these results into consideration we envisioned that under mild photochemical conditions the preparation of benzylboronates by homologation of boronic acids by reaction with N -tosylhydrazones might be possible.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we became inspired by some recent publications that reported that the decomposition of N -tosylhydrazones can be promoted photochemically. 17–20 In particular, König et al discovered that the formation of diazo compounds from N -tosylhydrazones can be achieved by irradiation of the N -tosylhydrazone salts with visible light at rt, and applied this reaction in the homologation of carbonyl compounds (Scheme 1e). 17 Taking these results into consideration we envisioned that under mild photochemical conditions the preparation of benzylboronates by homologation of boronic acids by reaction with N -tosylhydrazones might be possible.…”
Section: Introductionmentioning
confidence: 99%
“…To tackle some of these challenges, activation of either oxadiazolines or tosylhydrazones by energy transfer photocatalysis has been reported very recently. 27,28 Nevertheless, these methods require the addition of elaborate photocatalysts and can only access the corresponding carbene species directly without harnessing the unique reactivity of diazo compounds.…”
mentioning
confidence: 99%
“…[23][24][25] Inspired by the ring expansion of fluoroalkyl-N-triftosylhydrazones and azoles, [22] we continue to explore the reactivity of azoles with donor-type carbene precursors. In fact, aryl/aryl or aryl/alkyl carbenes of low reactivity [23][24][25] have drawn particular attention because they have been shown to efficiently introduce diarylmethylene or aryl/alkylmethylene units into a variety of organic building blocks [23][24][25][26][27][28][29] and that are readily converted from the corresponding aldehydes and ketones. In addition, based on our previous studies on the reaction of Ntriftosylhydrazones with silver catalysis, [30,31] we envisioned that the reactivity of donor-silver carbene intermediates could be enhanced by the weak interaction of silver with the carbene carbon to effectively form indazolium ylides with indazoles as a means of conversion to quinazolines.…”
Section: Introductionmentioning
confidence: 99%